2021
DOI: 10.1186/s40780-021-00202-1
|View full text |Cite
|
Sign up to set email alerts
|

Mixture of clopidogrel bisulfate and magnesium oxide tablets reduces clopidogrel dose administered through a feeding tube

Abstract: Background In clinical practice, a mixed suspension of clopidogrel bisulfate and magnesium oxide (MgO) tablets is administered frequently via a feeding tube. However, there is no report on the changes occurring when suspensions of these two drugs are combined, including the effects or potential decrease in dose following tube administration. Thus, the purpose of our study was to investigate the (i) changes caused by mixing clopidogrel bisulfate (ion form) and MgO tablets and (ii) effects on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Thus, it is necessary to evaluate the chemical stability of drugs concomitantly suspended with MgO under an SSM condition. Aoki et al [ 15 ] reported that no degradation occurred in the co-suspension of MgO and clopidogrel bisulfate, which has an ester moiety. On the contrary, Suryani et al [ 16 ] reported that when ester prodrugs, acemetacin and cefpodoxime proxetil, were subjected to the SSM with MgO, the ester bonds were hydrolyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to evaluate the chemical stability of drugs concomitantly suspended with MgO under an SSM condition. Aoki et al [ 15 ] reported that no degradation occurred in the co-suspension of MgO and clopidogrel bisulfate, which has an ester moiety. On the contrary, Suryani et al [ 16 ] reported that when ester prodrugs, acemetacin and cefpodoxime proxetil, were subjected to the SSM with MgO, the ester bonds were hydrolyzed.…”
Section: Introductionmentioning
confidence: 99%